2008
DOI: 10.1111/j.1365-2052.2007.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphisms in bovine fatty acid synthase are associated with beef fatty acid composition1

Abstract: The objective of this study was to identify single nucleotide polymorphisms (SNPs) in the thioesterase (TE) domain of the bovine fatty acid synthase (FASN) gene and to evaluate the extent to which they were associated with beef fatty acid composition. The four exons in FASN that encode for the TE domain were sequenced, and three SNPs, AF285607:g.17924A>G, g.18663T>C and g.18727C>T, were identified. Purebred Angus bulls (n = 331) were classified into three genotype groups, g.17924AA (n = 121), g.17924AG (n = 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 25 publications
5
122
5
1
Order By: Relevance
“…The increasing cost of large animal experiments, increased legislative requirements on the ethical use of animals (Radzikowski, 2006), together with considerable inter-animal variation in feed intake (Nkrumah et al, 2007), hepatic function (Dorroch et al, 2001), resistance to disease (Morris, 2007) and inherent fatty acid concentrations in cattle even within breeds fed the same diets (Pitchford et al, 2002) results in marked difficulties in investigating dietary effects on tissue fatty acid accretion. While there is notable genetic variation associated with beef fatty acid composition (Zhang et al, 2008), there is also variation in the expression of a number of genes controlling fatty acid constituents of beef, such as SREBP-1c (Hoashi et al, 2007) and D-9 desaturase (Lehnert et al, 2006). Consequently, the use of more controlled environments to test specific biological hypotheses is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing cost of large animal experiments, increased legislative requirements on the ethical use of animals (Radzikowski, 2006), together with considerable inter-animal variation in feed intake (Nkrumah et al, 2007), hepatic function (Dorroch et al, 2001), resistance to disease (Morris, 2007) and inherent fatty acid concentrations in cattle even within breeds fed the same diets (Pitchford et al, 2002) results in marked difficulties in investigating dietary effects on tissue fatty acid accretion. While there is notable genetic variation associated with beef fatty acid composition (Zhang et al, 2008), there is also variation in the expression of a number of genes controlling fatty acid constituents of beef, such as SREBP-1c (Hoashi et al, 2007) and D-9 desaturase (Lehnert et al, 2006). Consequently, the use of more controlled environments to test specific biological hypotheses is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…The FASN gene has seven active sites that help to catalyze all the reaction steps in the conversion of acetyl-CoA and malonyl-CoA to palmitate (Roy et al, 2005). Several reports indicated that the mutations in FASN gene were associated with (Bhuiyan et al, 2009;Lee et al, 2010;Zhang et al, 2008). Also, the polymorphisms in chicken FASN gene have been reported by Marrube et al (2004) and this gene is located on chromosome 18 and had three TE domains in exons 40, 41 and 42 (Kasturi et al, 1988).…”
Section: Introductionmentioning
confidence: 95%
“…Based on the previously study, TE domain within bovine FASN complex is responsible for termination of fatty acid synthesis (Zhang et al, 2008). In case of FASN gene in chicken liver, Kasturi et al (1988) observed that TE domain was located in exon 40-42 that might be also responsible for fatty acid analysis in chicken.…”
Section: Fasn and Scd Gene Effects To Fa Compositionmentioning
confidence: 99%
“…In addition, a health index (HI) was also calculated as the inverse of atherogenic index as originally proposed by Ulbricht & Southgate (1991) with a modification as described by Zhang et al (2008): HI = (total MUFA + total PUFA) / (4 x 14:0 + 16:0).…”
Section: Accepted Manuscriptmentioning
confidence: 99%